Progressive atrophic indurated plaques in a 16‐year‐old boy. (27th May 2021) - Shahid, A.; Shepherd, K.; Shivamurthy, V.; Lebas, E.; Calonje, E.; Baron, S.; Abdelrahman, W.
Abstract : Click here for the corresponding questions to this CME article.